Media Information and People's Self-motivated Behaviour during the COVID-19 Pandemic - Hitoshi Mitomo; John W. Cheng; Artima Kamplean; Yongkyoung Seo (International Telecommunications Society (ITS), 2023)
This paper quantitatively examines the impact of media information on people's self-motivated behaviour during the COVID-19 pandemic. Using a framework based Extended Parallel Process Model and data collected from Japan in 2021 (n=2660), it is found that fear appeals of COVID-19 from television news increase people's perceived threat of COVID-19 infection and perceived efficacy of COVID-19 prevention measures. These perceptions mediate the effects of the fear appeals on people's intention to follow voluntarily COVID-19 prevention measures requested by the Japanese government. The results also show that while hard news and soft news programmes have similar effects, hard news appears to have stronger effects on the fear appeals than that of soft news.
Keywords: 330